Patologías causadas por humedad para el caso de estudio en el conjunto residencial San Jerónimo de Yuste (2024)
The aim of this project is to develop a comprehensive overview of the pathologies associated with humidity in buildings, applying the findings to the San Jerónimo de Yuste residential complex. To this end, a systematic review of the literature was carried out, from which a guide was developed for the assessment of humidity in buildings by inspecting different items.